Mangandung Ritual in Batak Toba Society: A Musical and Cultural Perspective - Rosmegawaty Tindaon; M Halim; Rina Oktavia; Martis Martis; Yasril Adha (Pascasarjana Institut Seni Indonesia Padang Panjang, 2026)
Although ethnomusicological studies on Batak Toba traditions continue to develop, scholarly attention to the musical analysis of andung remains limited, particularly regarding its continuity and transformation within musical and cultural perspectives. This study examines the continuity and change of the mangandung ritual in Batak Toba funeral traditions, focusing on its musical dimensions. As a vocal expression of grief, andung embodies structured musical elements such as melody, rhythm, vocal ornamentation, and performance context. Using a qualitative ethnomusicological approach, this research employs field observation, in-depth interviews with tradition bearers, and audio-visual documentation. The analysis identifies patterns of continuity and transformation in andung singing. Findings reveal that while the ritual’s primary expressive function as a medium of lamentation is preserved, its musical characteristics have significantly changed. These include the simplification of melodic structures, reduced use of traditional ornamentation, and shifts in performance context influenced by modernization, religious practices, and contemporary funeral services. These changes reflect a dynamic negotiation between preservation and adaptation. The study underscores the importance of systematic documentation and pedagogical strategies to sustain the mangandung ritual and its transformation into andung as part of Batak Toba cultural heritage.